The Relationship of Group Cohesiveness to Decision Making on Consuming Electronic Cigarettes in FISH UNJ Female Students - Allifiansyah, Sandy; AKBAR, FIKRI; Azizah, Dinda Putri; Alifa, Inaya Aqilah; Rahma, Hafidzah Fatinah; Atsyah, Jasmine Syifa Shadrina; Purba, Rachel Margaret; Tridewi, Sylfani (Universitas Sang Bumi Ruwa Jurai, 2025)
This study examines the relationship between group cohesiveness and decision-making to consume e-cigarettes among female students at the Faculty of Social Sciences (FIS), State University of Jakarta (UNJ). Group cohesiveness is defined as the strength of bonds between group members, encompassing interpersonal attachment, shared goals, and group activities. The study adopts a quantitative approach using bivariate analysis methods, including normality tests, linearity tests, simple linear regression, t-tests, and chi-square tests, to analyze the influence of group cohesiveness on decision-making. The results reveal that while group cohesiveness has a positive relationship with the decision to consume e-cigarettes, the effect is not statistically significant. Key findings highlight that group cohesiveness is characterized by emotional closeness, social interaction, and a sense of belonging. However, decision-making regarding e-cigarette consumption is influenced more by individual comfort and social dynamics within the group. The study concludes that group cohesiveness, though important for fostering a sense of belonging and interaction, does not significantly drive the decision to consume e-cigarettes. This research underscores the need for educational programs to raise awareness of the positive and negative impacts of group cohesiveness and the health risks associated with e-cigarette use. Specific initiatives targeting female students are recommended to mitigate the adoption of risky behaviors influenced by peer groups.